Board of Editor - Journal of Infrastructure & Facility Asset Management (Journal of Infrastructure & Facility Asset Management, 2021)
Paper Writting StipulationPapers on JIFAM - The Journal of Infrastructure & Facility Asset Management Journal is regulated by general stipulation as follows.-          Papers must be a real work of the author.-          Papers has never been published in other media.-          Papers must contain discussion about Infrastructure & Facility Asset Management.-          Papers must contains a new discussion, judging based on the discussion that has been published in previous JIFAM.-          The paper has to take references from Scientific Journal with minimum of 5 papers.-          Paper lengths are limited in 8-16 pages.-          Paper Template can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifamScope of TopicJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited, of  the following.-          I & F Function-          I & F Demand - Supply-          I & F User Behavior-          I & F Policy-          I & F Planning-          I & F Administration Aspects-          I & F Operation System-          I & F Maintenance System-          I & F Evaluation Technique-          I & F Disposal-          I & F Economical Aspect-          I & F Financial Aspect-          I & F Management Organization-          I & F Spatial Aspects and Environmental Aspects